ACTIVITY OF NANO ENCAPSULED ANNATTO SEEDS AND BEETROOT EXTRACTS TO EXTENDING THE SHELF LIFE OF BEEF BURGER - Altaee, Z. H. A; Alrubeii, A. M. S.; Labeeb Ahmed Al-Zubaidi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The present study highlighted the effectiveness of natural extracts derived from annatto and beetroot in prolonging the shelf life of refrigerated beef burgers for up to 12 days. The experimental design included five treatment groups: T1 (control, no additives), T2 (185.6 µg/ml nano-encapsulated annatto), T3 (187.6 µg/ml nano-encapsulated beetroot), T4 (a combination of nano-encapsulated annatto and beetroot at the same concentrations), and T5 (0.01% BHA). Samples were stored under refrigeration for 1, 3, 6, 9, and 12 days, after which they were subjected to a series of physical, chemical, microbiological, and sensory evaluations. The data revealed that the nano-encapsulation of annatto and beetroot extracts led to statistically significant increases (P < 0.01) in protein, fat, and ash content, as well as elevated levels of myoglobin pigment and thiobarbituric acid (TBA) values. In contrast, moisture content and water-holding capacity (WHC) showed significant reductions (P < 0.01). These findings suggest that incorporating nano-formulated annatto and beetroot extracts into beef burgers contributes to enhanced antioxidant activity during chilled storage, as evidenced by lower oxidative indicators and reduced total bacterial counts.